Building Children's Independence through One Way Communication - Faizatul Widat; Ainil Hamdia; Alfiyah Alfiyah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This research is a research that combines the learning methods used by teachers, namely the one way communication method and the concept of early childhood independence. This research method is a qualitative type of case study. This research was conducted at the RA Hidayatul Islamiyah institution in Karangbong Village. The sources of information in this study are principals and teacher councils taken with a purposive sampling approach. The results of this study in training early childhood independence through one-way communication are as follows: first, planning for RPP as a reference for early childhood learning, supporting facilities for one-way communication and effective and efficient learning schedules. Furthermore, the implementation includes providing understanding in one-way communication, approaches to early childhood, using habituation techniques and learning media. Finally, evaluate the teacher's strategy in doing one-way communication, the value of independence taught, and early childhood has good independence.